THE USE OF DISCUSSION ACTIVITY FOR IMPROVING SPEAKING SKILLS IN THIRD SEMESTER STUDENTS - Dede Narawaty (Universitas Nasional, 2022)
AbstractThis research was conducted at Indraprasta University PGRI, majoring in English. In additon, this research focuses on students in the third semester. This research was conducted based on the idea that speaking is one of the skills in English that every student must have. This is because speaking is a language skill that has a deep bond with human life. This research uses descriptive qualitative method. The researcher uses the listening method, asfollows in the form of tapping techniques to collect data, then the results of the researchers' observation in observing Researchers using the listening technique and tapping techniques to see the difference in the scores of the students before and after this research. Then, the results of the researchers'will be taken from the observations in observing their discussion activities. Based on the observations, the lecturer has implemented steps to conduct discussions. The researchers used four stages in their research to see the differences in students' abilities. As for the results of the study, the students were able to increase the score of their English speaking abilities in four research cycles, using discussion techniques. Their success cannot be separated from their ability to overcome worries of making mistakes in EnglishKeyword: students, speaking, abilities, discussion, score AbstrakPenelitian ini dilaksanakan di Universitas Indraprasta PGRI, jurusan bahasa Inggris. In additon, penelitian ini fokus pada para mahasiswa di semester tiga. Penelitian ini diadakan berdasarkan pemikiran, bahwa berbicara adalah salah satu skills dalam bahasa Inggris yang harus dimiliki setiap mahasiswa. Hal ini disebabkan, karena berbicara adalah suatu keterampilan berbahasa yang memiliki ikat an yang mendalam dengan kehidupan manusia. Penelitian ini menggunakan metode kualitatif deskriptif. Kemudian Peneliti menggunakan teknik menyimak dan sadap untuk mengumpulkan data, kemudian hasil simakan peneliti dalam mengamati Peneliti menggunakan metode simak yaitu berupa teknik sadap untuk mengumpulkan data, kemudian hasil simakan peneliti dalam mengamati untuk melihat perbedaan nilai para mahasiswa sebelum dan sesudah penelitian. Berdasarkan hasil pengamatan, dosen sudah menerapkan langkahlangkah untuk melakukan diskusi. Para peneliti menggunakan empat stages dalam penelitiannya guna melihat perbbedaan kemampuan para mahasiswa. Adapaun hasil penelitian adalah para mahasiswa mampu menaikkan score their English speaking abilities dalam masa empat siklus penelitian, denagn menggunakan teknik diskusi. Keberhasilan mereka tidak lepas dari kemampuan mereka mengatasi kekhawatiran membuat kesalahan dalam baerbahasa InggrisKata kunci: siswa, berbicara, kemampuan, diskusi, nilai